LEGAL ACTION AGAINST WITHDRAWALWAKAF PROPERTY(Decision Study No. 22/Pdt.G/2017/MS-Aceh) - Jiko (Jurnal Legislasi dan Pembentukan Peraturan Perundang-undangan, 2025)
Withdrawal of Waqf Assets based on Decision No. 22/Pdt.G/2017/MS-Aceh because the objects which are waqf assets belonging to the Bireueen Islamic Education Society have been misused by the Bireueen Ministry of Religious Affairs in a dysfunctional manner, namely the waqf objects are recorded as Public Property. In order for the irregularity of the waqf assets to be in accordance with the waqf pledge made, the owner of the waqf rights takes over the waqf assets. The validity of Nazir as the owner of the waqf rights in the event of misappropriation of waqf assets based on Resolution no. 22/Pdt.G/2017/MS-Aceh is reviewed from the provisions of Article 42 of Law Number 41 of 2004 concerning Waqf which explains: "It is the duty of nazhir to manage and dispose of waqf assets for their intended use, according to their function and designation." So that the waqf assets that were originally borrowed by the owner of the waqf rights can be disposed of if there is misuse of waqf assets. The Judge's reason for permitting the takeover of misused waqf assets in Decision no. 22/Pdt.G/2017/MS-Aceh, based on the findings of the facts by the Judge, is of the opinion that legally there is no legal justification for the Defendant/Applicant to hold objects that are unlawfully and unlawfully owned and managed as YPI Bireuen's claim property.